Novel hybrid strong and weak PUF design based on FPGA - Jiana LIAN; Pengjun WANG; Gang LI; Xuejiao MA; Guanbao ZHAI (网络与信息安全学报)
Physically unclonable function (PUF) can produce intrinsic keys with characteristics of randomness, uniqueness and tamper-proof by exploiting the process deviations which can not be avoided in the chip manufacturing process.A novel hybrid strong and weak PUF (SWPUF) circuit design based on field-programmable gate array(FPGA) was proposed after the investigation of the PUF circuit structures and principles.To address the limitation of designing strong-PUF and weak-PUF discretely, SWPUF could be configured into two topologies conveniently depending on the Hamming Weight (HW) of the challenges.In addition, the statistical characteristics of the responses could be further improved by a XOR-decorrelation technique.The proposed SWPUF was implemented on a Xilinx Artix-7 FPGA (28nm technology), and a self-built test platform was set up by using Matlab and MicroBlaze microcontroller.Experimental results show that the SWPUF has good performances of randomness (96.98%), uniqueness (99.64%) and reliability (96.6%).Logic register analysis also shows that the SWPUF has a better anti-attack capability than the traditional Arbiter-PUF in the case of with small HW, and can be used in the information security, such as key storage (especially to weak PUF) and device authentication (especially to strong PUF).